2021
DOI: 10.1007/s42452-020-04104-z
|View full text |Cite
|
Sign up to set email alerts
|

Potential flood frequency analysis and susceptibility mapping using CMIP5 of MIROC5 and HEC-RAS model: a case study of lower Dwarkeswar River, Eastern India

Abstract: Floods are one of the major concerns in the world today. The lower reaches of the river coming from the western side of West Bengal are often affected by floods. Thereby estimation and prediction of flood susceptibility in the light of climate change have become an urgent need for flood mitigation and is also the objective of this study. The historical floods (1978–2018) of the monsoon-dominated lower Dwarkeswar River, as well as the possibility of future floods (2020–2075), were investigated applying peak flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…Heavy rainfall during monsoon leads to destructive flash floods in the Darjeeling district located in the north of the sub‐basin (Karmokar & De, 2020). In addition, the paleo‐flood records revealed that flood intensity has been increasing in West Bengal over the period of time (Malik & Pal, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heavy rainfall during monsoon leads to destructive flash floods in the Darjeeling district located in the north of the sub‐basin (Karmokar & De, 2020). In addition, the paleo‐flood records revealed that flood intensity has been increasing in West Bengal over the period of time (Malik & Pal, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This study tries to map the flood susceptibility in the Bhagirathi sub-basin using hybrid frequency ratio and Shannon entropy model. Earlier works (Kaur et al, 2017;Malik & Pal, 2021) on susceptibility assessments F I G U R E 1 Location of the sub-basin in India: (A) sub-basin divisions and watersheds and (B) previous flood sites were often found subjective in nature while in this study probability of flood susceptibility was calculated for each parameter using entropy information theory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selecting an acceptable method is thought to be a vital step for researchers in flood susceptibility mapping. According to Souissi et al, 2020, The four major approaches utilised in flood susceptibility research are as follows: (1) a bivariate statistics techniques like logistical regression method (Al-Juaidi et al, 2018;Chowdhuri et al, 2020), certainty factor (Cao et al, 2020), frequency-dependent statistic (Samanta et al, 2018;Rahmati et al, 2016), evidencebased weighting (Rahmati et al, 2016), (2) strategies based on expert knowledge or MCDA techniques like the method for Sorting Preferences by Comparison to the Perfect Solution (Razavitermeh et al, 2018), AHP (Hamlat et al, 2021;Choudhury, 2022), (3) Utilising hydrological techniques as the Soil Water Analysis System (Malik et al, 2021), and (4) Machine learning techniques , such support vector machines (Tehrany et al, 2015;Youssef et al, 2023).…”
Section: Egyptian Railway Authoritymentioning
confidence: 99%
“…The study also provided potential adaptation strategies. Malik & Pal (2021) analyzed the flood susceptibility of the lower Dwarkeswar River for historical and future floods for one GCM using the HEC-RAS rain-on-grid model. They concluded that Weibull's method was the best suited for flood susceptibility mapping.…”
Section: Introductionmentioning
confidence: 99%